Comparative Analysis of Digital Banks’ Financial Performance Based on Profitability Ratios (A Case Study: Allo Bank and Bank Neo Commerce (BNC) in the 2021-2023 Period) - Saswita Sianipar, Rica; Galuh, Ajeng Kartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The digital banking industry has become the center of attention in the era of ever-growing digitalization. In this context, financial performance analysis is crucial for understanding the effectiveness and sustainability of digital banks. This research aims to analyze and compare the economic performance of two leading digital banks in Indonesia, namely Allo Bank and Neo Commerce Bank, based on profitability ratios. By utilizing financial report data for the 2021-2023 period, this research uses a comparative descriptive analysis method to evaluate the economic performance of the two banks. Data analysis uses 2 different tests, the Independent Sample Test and the Mann Whitney-Test using SPPS 21. The research results show that Net Profit Margin (NPM), Return On Assets, Return On Equity, and Return On Investment (ROI) are partially different. Significant between 2 digital banks Allo Bank and Bank Neo Commerce (BNC).